Influence of “mild” stress on the level of biochemical markers of pathology in the submandibular glands of rats - Yuzkiv, Ya. (Journal of Education, Health and Sport, 2025)
Background. Stress is one of the important causes of the development of pathological processes in the body. The salivary glands play a certain role in the pathogenesis of post-stress pathological reactions Aim. To determine the state of the submandibular gland of rats after "mild" stress (−20 °C, 5 minutes) by such indicators as proteolysis, kallikrein-kinin system, and oxidation. Methods. The state of proteolysis was assessed by the rate of casein hydrolysis (pH 7,6) according to the Kunitz method, the state of the kallikrein-kinin system was determined by the rate of BAEE (benzoyl-arginine ethyl ether) hydrolysis, and the oxidation activity was determined by the rate of ascorbic acid oxidation. Results. It has been established that in rats after stress, the level of proteolysis increases (significantly after 24 hours) and the level of oxidation increases very strongly (almost 6 times). The activity of BAEE esterase does not significantly respond to “mild” stress. Conclusion. The submandibular gland is sensitive to "mild" stress, increasing the activity of oxidation and proteolysis processes.